Hypoxia-inducible factor-2α is essential in activating the COX2/mPGES-1/PGE(2) signaling axis in colon cancer - Xue, Xiang (Oxford University Press, 2013)
Cyclooxygenase 2 (COX2) is overexpressed in 80% of colon adenocarcinomas. However, the mechanism leading to aberrant COX2 expression in tumors is unclear. Intestinal epithelium-specific disruption of the von Hippel–Lindau tumor suppressor protein (VHL) in adenomatous polyposis coli (Apc)(min/+) mice (Vhl(ΔIE)/Apc(min/+)) resulted in constitutive activation of hypoxia-inducible factor (HIF), robustly enhanced colon carcinogenesis and potentiated COX2 expression in normal colon epithelium and tumors. In this study, we hypothesize that HIF regulates COX2 expression in colon tumors, and this regulation is critical for HIF-mediated colon carcinogenesis. COX2 was demonstrated to be a direct target gene of HIF-2α, and genetic disruption of HIF-2α abolished the induction of COX2 in tumors. Furthermore, inhibition of COX2 by nimesulide reduced HIF-2α-induced colon tumor formation. Interestingly, the levels of prostaglandin E(2) (PGE(2)), the downstream effector of COX2, remained elevated in normal and tumor tissues of the nimesulide-treated Vhl(ΔIE)/Apc(min/+) mice. Further examination revealed that the terminal PGE(2) synthesis enzyme microsomal prostaglandin E synthase 1 (mPGES-1) was overexpressed in the colon of Vhl(ΔIE)/Apc(min/+) mice. mPGES-1 was demonstrated to be a direct target gene of HIF-2α, and genetic disruption of HIF-2α abolished the induction of mPGES-1 in colon tumors. Together, our findings demonstrate that HIF-2α is a major regulator of COX2/mPGES-1/PGE(2) pathway in colon tumors.